The Analysis of Social and Discourse Deixes in the ‘Bird Box’ Novel by Josh Malerman - Chairina Nasir; Aulia Putri; Zulfadli Aziz (Journal of English Education and Teaching, 2023)
Many representations of human thoughts, ideas, opinions, and messages are portrayed in diverse situations of the character in literary works. Among the works are such as novels. Deixis is concerned with the encoding of many different aspects of the circumstances surrounding the utterances and within the utterances themselves. This study aims to find out the type of social deixis and discourse deixis used in the novel ‘‘Bird Box’’ written by Josh Malerman, published in 2014. The research design used is the qualitative approach with document analysis as the data collection technique. Cruse’s theory (2000) is applied to analyze the data related to the types of social deixis and discourse deixis found in the novel. The results of this research show that there are 475 data containing social deixis and discourse deixis, with 317 data of social deixis (of these, 307 data are related to relational social deixis and 10 data are related to absolute social deixis), and 158 data of discourse deixis. Understanding deixis, especially while reading works like novels, is a means to understanding the plot as well as the characters portrayed and to reduce the amount of ambiguity. Moreover, using the proper deictic words will help foreign language learners, such as English non-native students, in their efforts to produce effective communication, whether in spoken or written forms. Keywords: deixis; social deixis, discourse deixis; novel